Symptomatic Perianeurysmal Edema Following Bare Platinum Embolization of a Small Unruptured Cerebral Aneurysm - Craven, I.; Patel, U.J.; Gibson, A.; Coley, S.C. (American Journal of Neuroradiology, 2009)
SUMMARY: There is considerable interest in the development of symptomatic inflammatory reactions following coil embolization of cerebral aneurysms. Patients have experienced a range of adverse events, usually after treatment of moderately large aneurysms with modified “bioactive” coils. More recently, it has been recognized that adverse inflammatory reactions can be associated with the use of “nonbioactive” coils, and we present a case of symptomatic perianeurysmal edema after treatment of a small unruptured aneurysm with bare platinum coils.